Gender separation and the speech community: Rhoticity in early 20th century Southland New Zealand English. (July 2021) - Villarreal, Dan; Clark, Lynn; Hay, Jennifer; Watson, Kevin
Abstract: The existence of a shared constraint hierarchy is one of the criteria that defines and delimits speech communities. In particular, women and men are thought to differ only in their rates of variable usage, not in the constraints governing their variation; that is, women and men are typically considered to belong to the same speech community. We find that in early twentieth century Southland, New Zealand, women and men had different constraint hierarchies for rhoticity, with a community grammar of rhoticity only developing later. These results may be a product of a particular set of sociohistorical facts thatare not peculiar to Southland. We suggest that further research in other geographical locations may indeed reveal that men and women have different constraint hierarchies for other variables. Speech communities may thus be delimited along social lines in ways that have not been previously considered.